Local application of engineered insulin-like growth factor I mRNA demonstrates regenerative therapeutic potential in vivo - Justin S. Antony; Pascale Birrer; Claudia Bohnert; Sina Zimmerli; Petra Hillmann; Hervé Schaffhauser; Christine Hoeflich; Andreas Hoeflich; Ramzi Khairallah; Andreas T. Satoh; Isabelle Kappeler; Isabel Ferreira; et al. (Elsevier, 2023)
Insulin-like growth factor I (IGF-I) is a growth-promoting anabolic hormone that fosters cell growth and tissue homeostasis. IGF-I deficiency is associated with several diseases, including growth disorders and neurological and musculoskeletal diseases due to impaired regeneration. Despite the vast regenerative potential of IGF-I, its unfavorable pharmacokinetic profile has prevented it from being used therapeutically. In this study, we resolved these challenges by the local administration of IGF-I mRNA, which ensures desirable homeostatic kinetics and non-systemic, local dose-dependent expression of IGF-I protein. Furthermore, IGF-I mRNA constructs were sequence engineered with heterologous signal peptides, which improved in vitro protein secretion (2- to 6-fold) and accelerated in vivo functional regeneration (16-fold) over endogenous IGF-I mRNA. The regenerative potential of engineered IGF-I mRNA was validated in a mouse myotoxic muscle injury and rabbit spinal disc herniation models. Engineered IGF-I mRNA had a half-life of 17-25 h in muscle tissue and showed dose-dependent expression of IGF-I over 2-3 days. Animal models confirm that locally administered IGF-I mRNA remained at the site of injection, contributing to the safety profile of mRNA-based treatment in regenerative medicine. In summary, we demonstrate that engineered IGF-I mRNA holds therapeutic potential with high clinical translatability in different diseases.